2014
DOI: 10.1155/2014/310680
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mycotoxin Deoxynivalenol on Haematological and Biochemical Indicators and Histopathological Changes in Rainbow Trout (Oncorhynchus mykiss)

Abstract: Deoxynivalenol (DON), produced by the Fusarium genus, is a major contaminant of cereal grains used in the production of fish feed. The effect of mycotoxin deoxynivalenol on rainbow trout (Oncorhynchus mykiss) was studied using a commercial feed with the addition of DON in a dose of 2 mg/kg feed. The fish (n = 40) were exposed to the mycotoxin for 23 days. The trout were divided into two groups, control and experimental groups. Control groups were fed a commercial feed naturally contaminated with a low concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…A recent investigation of zebrafish Danio rerio fed DON at concentrations of 0.1-3 mg/kg feed showed higher levels of genetic liver biomarkers and an influence on the reproductive system (Sanden et al 2012). In a previous study we found changes in haematological and biochemical parameters, including pathological alterations in caudal kidney, of rainbow trout fed DON at 2 mg/kg feed (Matejova et al 2014). Woodward et al (1983) found that diets containing 1.0-12.9 mg/kg DON depressed feed intake and weight gain and decreased feed conversion efficiency of juvenile rainbow trout.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…A recent investigation of zebrafish Danio rerio fed DON at concentrations of 0.1-3 mg/kg feed showed higher levels of genetic liver biomarkers and an influence on the reproductive system (Sanden et al 2012). In a previous study we found changes in haematological and biochemical parameters, including pathological alterations in caudal kidney, of rainbow trout fed DON at 2 mg/kg feed (Matejova et al 2014). Woodward et al (1983) found that diets containing 1.0-12.9 mg/kg DON depressed feed intake and weight gain and decreased feed conversion efficiency of juvenile rainbow trout.…”
mentioning
confidence: 79%
“…No morbidity and mortality was recorded during the study. The same animals were used as in an already published study (Matejova et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These equivalents were prepared in place of 3 mg and 5.4 mg, respectively as up to 33% loss of T2‐toxin was expected during the preparation of pellets with such a small amount of active substance. This level of loss has been experimentally verified when preparing pellets by the same method with other substances (Matejova et al., , ).…”
Section: Methodsmentioning
confidence: 57%
“…After 23‐d exposure to DON in a concentration of 2.0 mg/kg, rainbow trout showed severe hyaline droplet degeneration in tubular epithelial cells of the renal tubules in the caudal kidney. Although no significant changes in biometric parameters were recorded, significant changes in hematological parameters, such as lower mean corpuscular hemoglobin values, and biochemical parameters, such as a decrease in glucose, cholesterol, and ammonia, were observed (Matejova et al ).…”
Section: Fusarium Mycotoxinsmentioning
confidence: 99%